2019
DOI: 10.1037/aap0000157
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between ethnocultural identity measures and youth substance use among a school-based sample: A focus on Native Hawaiian youth.

Abstract: The way in which behavioral health interventions are designed, implemented, and evaluated must be responsive to the ethnocultural characteristics of the targeted youth and their families, schools, and communities. The goal of this article is to examine the relationship between ethnocultural identity measures and substance use among Native Hawaiian compared with non-Hawaiian youth. A crosssectional analysis was conducted from baseline data drawn from an efficacy trial of a culturally grounded drug prevention cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Research investigating ethnocultural identity has shown that for NH youth, identity serves as a protective factor against SU (Helm et al, 2019). Recent efficacy trials for the Hoʻouna Pono school-based culturally grounded SU prevention curriculum have shown promising results of preventing SU among NH youth in rural communities (Okamoto et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Research investigating ethnocultural identity has shown that for NH youth, identity serves as a protective factor against SU (Helm et al, 2019). Recent efficacy trials for the Hoʻouna Pono school-based culturally grounded SU prevention curriculum have shown promising results of preventing SU among NH youth in rural communities (Okamoto et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this is primarily an urban sample of Native Hawaiian youth who may qualitatively describe the relationship between place and self very differently from youth living entirely in rural locations. Hawai’i is unique and quite diverse ethnoculturally and there are differences geographically across the islands and within and across groups (Helm et al, 2019). Hence, we cannot generalize to all Native Hawaiians based on our small sample.…”
Section: Discussionmentioning
confidence: 99%
“…They report that 1.5 million people in the U.S. identified as Native Hawaiian or other Pacific Islander and this group represents one of the fastest-growing cultural groups in the U.S.. The term “Native Hawaiians” refer to the indigenous people of Hawai’i, comprising about 25% of the population of the state (Helm et al, 2019).…”
Section: Why Native Hawaiians?mentioning
confidence: 99%
“…Four of the articles in this special issue are specifically focused on the behavioral health of Native Hawaiians and other Pacific Islanders. Two of these articles (Helm, Hishinuma, Okamoto, Chin, & Silva, 2019; Wills, Okamoto, Knight, & Pagano, 2019) are focused on psychosocial risk and protective factors in Native Hawaiian and other Pacific Islander youth and have implications for informing the development of culturally responsive youth interventions. The other two behavioral health articles in this special issue (Okamoto et al, 2019; Yamada, Vaivao, & Subica, 2019) are focused on the evaluation of culturally responsive interventions for Native Hawaiians and Samoans, respectively.…”
Section: Overview Of the Studies In This Special Issuementioning
confidence: 99%
“…The other two behavioral health articles in this special issue (Okamoto et al, 2019;Yamada, Vaivao, & Subica, 2019) are focused on the evaluation of culturally responsive interventions for Native Hawaiians and Samoans, respectively. Helm et al (2019) examined the relationship between selected ethno-cultural identity items from two scales -The Hawaiian Culture Scale (Hishinuma, et al, 2000) and the Multiethnic Identity Measure (Phinney, 1992)-and substance use in rural Native Hawaiian youth. They found a significant inverse relationship between Native Hawaiian identity (primarily measured by Hawaiian language proficiency and maintaining Hawaiian cultural traditions) and the number of offers to use alcohol, tobacco, and/or other drugs for Native Hawaiian youth.…”
Section: Behavioral Healthmentioning
confidence: 99%